2019
DOI: 10.3389/fphys.2018.01872
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Changes During the Development of Artemia franciscana, From Cysts to the First Two Naupliar Stages

Abstract: The brine shrimp Artemia is an interesting experimental system for studies of developmental processes. Hatching of dormant cysts gives rise to shrimp larvae called nauplii, characterized by numerous naupliar stages representing the first forms of brine shrimp life cycle. Here combined Thin Layer Chromatography (TLC) and Matrix-Assisted Laser Desorption Ionization-Time-of-Flight/Mass Spectrometry (MALDI-TOF/MS) analyses have been performed to gain information on the lipid profiles of cysts and two naupliar stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…coli and S. aureus were predominantly phosphatidyl cholines (PCs) and phosphatidyl ethanolamines, which is consistent with previous research. , Using these feature lipid biomarkers, hierarchical clustering analysis (HCA) results showed that each type of treatment for E. coli and S.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…coli and S. aureus were predominantly phosphatidyl cholines (PCs) and phosphatidyl ethanolamines, which is consistent with previous research. , Using these feature lipid biomarkers, hierarchical clustering analysis (HCA) results showed that each type of treatment for E. coli and S.…”
Section: Resultssupporting
confidence: 90%
“…As suggested by identified lipid species, the feature phospholipids of E. coli and S. aureus were predominantly phosphatidyl cholines (PCs) and phosphatidyl ethanolamines, which is consistent with previous research. 72,73 Using these feature lipid biomarkers, hierarchical clustering analysis (HCA) results showed that each type of treatment for E. coli and S. aureus can be classified into their corresponding groups (Figure 5f,g). The results suggested that lipids responsible for metabolism regulation in the E. coli and S. aureus strains were disturbed by the different antibacterial treatments.…”
Section: Loading and Antioxidant Activity Of Cur In Cuppsimentioning
confidence: 99%
“…Lipids were then spotted onto the silica gel TLC plate and polar lipids were eluted with solvent A (chloroform/methanol/acetic acid/water 85:15:10:3.5, by volume). Phospholipid detection was carried out by spraying the plate with molybdenum blue spray reagent (Sigma‐Aldrich) (Lopalco et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The nutritional composition of different feeds used in this experiment was found to have different nutritional values. Newly hatched Artemia contain 57.26% protein, 16.21% fat and 6.67% carbohydrate) [27] (Brachionus rotifer contains 59.0% protein, 13.0% fat and 3.1% highly unsaturated fatty acid) [28] (Shrimp larvae commercial feed used in this study contains 48.0% protein, 9.0% fat, 2.5% ash and 9% moisture (Lansy-Shrimp PL (INVE ® , Phichit, Thailand). Although live feeds provide an excellent source of nutrition, several limitations are associated with their use.…”
Section: Survival Ratesmentioning
confidence: 99%